Tashmim Al’ab Lughawiyah Li Ta’limi Al-Lughah Al-‘Arabiyah Lil Mubtadiin Min Khilal Al-Kalimati Al-Minangkabawiyah Dzatu Aslin ‘Arabi Fi Qomus ( Bahasa Indonesia – Minangkabau ) Min Harfi “ N “ Ila “ Z “ - Alfi Hamdi; Abdurrahman Hilabi; Nazarudin Hanif (Mauriduna: Journal of Islamic Studies, 2021)
هدفت هذه الدراسة إلى اكتشاف الكلمات المينانجكابوية ذات أصل عربي في قاموس (Bahasa Indonesia – Minangkabau) من حرف "N" إلى "Z"، وهدفت هذه الدراسة إلى معرفة تغير معنى الكلمات العربية بعد دخولها في اللغة المينانجكابوية مع تصميم ألعاب اللغوية من تلك الكلمات لمساعدة المبتدئين في تعليم اللغة العربية. الدراسات تكون بالمنهج الوصف التحليلي. وأثبت الباحث منها بوجود الكلمات المينانجكابوية ذات أصل عربي في قاموس (Bahasa Indonesia - Minangkabau) من حرف "N" إلى "Z" بلغ عددها ثلاثة وثمانون (83) كلمة. وتواصل الباحث إلى وجود التغيرات في الكلمات العربية بعد دخولها في اللغة المينانجكابوية إلى أربعة أقسام كما يتواصل الباحث إلى طرق تصميم ألعاب اللغوية من تلك الكلمات على حسب المهارات الأربع لمساعدة المبتدئين في تعليم اللغة العربية. The purpose of this study is to point out absorbed Minangkabau Words from Arabic in “Bahasa Indonesia – Minangkabau“dictionary from the “N“ to “Z“, and to know meaning’s change from each words in Minangkabau language, and also the aim from this study is how to design language games from these words to help first grade students in their study for Arabic. The study is use method includes an analytical description. And the researcher proved presence of words Minangkabau of arab origin in dictionary (Bahasa Indonesia-Minangkabau) from letter “N” to “Z” reach eighty three (83) letter. And the reseach found meaning’s change when the words are absorbed from arabic to Minangkabau language, and these changes are in four types. And the research found methods of designing language games from these words to help first grade students in their study for Arabic, and these method are in the four language skills.